Preparation method of aramid nano-microsphere and ceramic mixed coating slurry and diaphragm

By introducing methylene or ether bonds into the meta-aramid main chain to form aramid nanospheres, and combining them with ceramic particles to prepare coating slurries, the problem of insufficient performance of existing lithium-ion battery separator materials has been solved and achieved High performance diaphragm material.

CN119350935AActive Publication Date: 2025-01-24TAYHO BATTERY MATERIALS TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411897043.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The liquid absorption rate, thermal stability and mechanical strength of existing lithium-ion battery separators are poor, affecting battery safety and performance.

Method used

By introducing methylene or ether bonds into the meta-aramid main chain, aramid nanospheres are formed and combined with ceramic particles to prepare a coating slurry to accurately control the coating thickness and improve the performance of the separator.

Benefits of technology

The high infiltration, high -breaking film temperature, excellent thermal resistance, and easy -to -control coating thickness of the diaphragm have been realized, and the safety and cycle life of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350935A_ABST
    Figure CN119350935A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to an aramid nano-microsphere and ceramic mixed coating slurry and a preparation method of a diaphragm, and the preparation method of the coating slurry comprises the following steps: in an organic solvent, when meta-aramid is subjected to polymerization reaction, introducing methylene or ether bonds to a meta-aramid main chain to obtain a modified meta-aramid stock solution; introducing the modified meta-aramid stock solution and a precipitation solvent into precipitation equipment, carrying out high-speed shearing treatment by the precipitation equipment, cooling and washing to obtain modified aramid nano-microspheres; and uniformly dispersing the aramid nano-microspheres, the ceramic particles, the thickening agent, the binder and the wetting agent in water to obtain the coating slurry. And uniformly coating a base membrane with the coating slurry, and then carrying out drying treatment to obtain the diaphragm. The diaphragm disclosed by the invention has the characteristics of good wettability, high diaphragm rupture temperature, high puncture strength, excellent heat resistance and easiness in controlling the coating thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing aramid nanometer microspheres and ceramic mixed coating slurry and a diaphragm, belonging to the technical field of battery materials. Background Art

[0002] Lithium-ion batteries have played an increasingly important role in electronic products and electric vehicles due to their advantages such as high operating voltage, high energy density, and long cycle life. However, with the increasing application of lithium-ion batteries, some safety issues have become more and more prominent. One of the most important components to ensure battery safety is the separator, which is located between the positive and negative electrodes and prevents physical contact between the electrodes while enabling free ion transmission and isolating electron flow.

[0003] At present, most commercial lithium-ion battery separators are usually made of polyolefin materials, such as polyethylene (PE), polypropylene (PP) and their mixtures. However, these materials often have poor liquid absorption, thermal stability and mechanical strength, which seriously affects the safety of the battery and limits the application of PP and PE. Therefore, the performance of the separator is improved by modification. Conventional methods include surface coating, surface grafting, blending, etc. Among these modification methods, surface coating has received the greatest attention as a strategy to improve the performance of the separator. Currently, it is common on the market to coat a layer of inorganic aluminum oxide (Al2O3) powder or silicon dioxide (SiO2) on a PE base film or a PP base film to improve the puncture resistance and thermal shrinkage of the separator. For example, Chinese patent application CN110444714A provides a ceramic aramid coated separator for lithium-ion batteries and a preparation method thereof. The aramid fiber is dissolved in N,N-dimethylacetamide (DMAC)-lithium chloride (LiCl) solution, and nano-Al2O3 particles and inorganic ceramic particles are coated on the separator to form a separator coating material with a 3D stereoscopic pore structure. However, the wettability and membrane rupture temperature need to be improved, and the heat resistance at higher temperatures cannot be met. Other heat resistance performances involving aramid coated diaphragms have not reached a higher level. Aramid has excellent mechanical properties, flame retardancy, heat resistance and electrical insulation properties, but the oily aramid coated diaphragm is expensive, thick and difficult to control. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics and a diaphragm. The addition of methylene or ether bonds increases the flexibility of the molecular chain, causing the molecular chain to curl into low-molecular-weight aramid nano-microspheres. The aramid nano-microspheres are combined with ceramic particles to obtain a coating slurry, thereby being able to more accurately control the coating thickness. The diaphragm has the characteristics of good wettability, high film rupture temperature, excellent heat resistance, and easily controllable coating thickness.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics, the preparation method comprising: S1. Preparation of modified meta-aramid stock solution: In an organic solvent, during the polymerization reaction of meta-aramid, a methylene group or an ether bond is introduced into the main chain of the meta-aramid to obtain a modified meta-aramid stock solution; S2. Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent are introduced into the precipitation device, subjected to high-speed shearing treatment by the precipitation device, cooled and then washed to obtain the modified aramid nano-microspheres; S3. Preparation of coating slurry: The coating slurry is obtained by uniformly dispersing aramid nano-microspheres, ceramic particles, a thickener, a binder and a wetting agent in water.

[0006] Furthermore, in step S1, the preparation process of introducing methylene groups into the meta-aramid main chain to prepare the modified meta-aramid stock solution is as follows: Dissolving m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane in DMAC, and after being completely dissolved, performing a low-temperature polycondensation reaction, and after the reaction is completed, neutralizing and filtering the product to remove unreacted raw materials to obtain a methylene-substituted modified m-aramid stock solution; The preparation process of introducing ether bonds into the meta-aramid main chain to prepare modified meta-aramid stock solution is as follows: Dissolve meta-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether in DMAC, and after they are completely dissolved, perform a low-temperature polycondensation reaction. After the reaction is completed, neutralize and filter the product to remove unreacted reagents to obtain an ether-bonded modified meta-aramid stock solution.

[0007] Furthermore, in the process of preparing the modified meta-aramid stock solution by introducing methylene groups into the meta-aramid main chain, the mass fraction of 4,4'-diaminodiphenylmethane in the modified meta-aramid polymer is 2%-30%; the molar ratio of the total molar number of meta-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:(0.95-1.05); In the process of preparing the modified meta-aramid stock solution by introducing ether bonds on the meta-aramid main chain, the mass fraction of 4,4'-diaminodiphenyl ether in the modified meta-aramid polymer is 2%-30%; the molar ratio of the total molar number of meta-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:(0.95-1.05).

[0008] Furthermore, the low-temperature polymerization reaction temperature is 5-10°C, and the reaction time is 1-2h.

[0009] Furthermore, the precipitation solvent includes water, DMAC and calcium chloride; the mass ratio of water, DMAC and calcium chloride is 100: (30-40): (2-4); the temperature of the precipitation solvent is 30-40°C.

[0010] Furthermore, the solid content of the modified meta-aramid stock solution is 12-18%; the mass ratio of the modified meta-aramid stock solution to the precipitation solvent is 1:(5-20); In step S2, the stirring speed of the high-speed shear treatment is 1500-3000 r / min.

[0011] Furthermore, in step S3, the mass ratio of the water, aramid nanospheres, ceramic particles, thickener, binder and wetting agent is (22-25):1:(6-8):(0.05-0.07):(0.5-0.7):(0.05-0.07).

[0012] Furthermore, the ceramic particles are at least one of aluminum oxide, silicon dioxide, magnesium hydroxide, zirconium dioxide, magnesium oxide, and boehmite.

[0013] Furthermore, the thickener is at least one of a cellulose thickener, an inorganic salt thickener and an amine oxide thickener; The binder is at least one of methyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; The wetting agent is at least one of siloxanes, fatty alcohol ethers and polyoxyethylene ethers.

[0014] The present invention also discloses a method for preparing a aramid nano-microsphere and ceramic mixed coated diaphragm, wherein the diaphragm is prepared by uniformly coating a coating slurry on a base film and then drying the diaphragm; the coating slurry is prepared according to the preparation method of the present invention.

[0015] The beneficial effects of the present invention are: In the preparation method of the aramid nano-microsphere and ceramic mixed coating slurry of the present invention, methylene or ether bonds are introduced into the main chain of poly(m-phenylene isophthalamide) to increase the flexibility of the molecular chain, and fine precipitated fibers are formed under high-speed shear stirring. Due to the addition of methylene or ether bonds, the flexibility of the meta-aramid molecular chain is increased, so that the molecular chain is curled into low-molecular-weight nano-microspheres. The particle size of the aramid nano-microspheres can be controlled by controlling the introduced groups and high-speed shear treatment conditions, and ceramic particles of different particle sizes are matched, so that the coating thickness can be more accurately controlled.

[0016] The diaphragm prepared by the preparation method of the present invention has the characteristics of good wettability, high film breaking temperature, high puncture strength, excellent heat resistance, and easy control of coating thickness. In addition, the present invention coats the aramid nano-microspheres, ceramics, binders, thickeners, and wetting agents to prepare a coating slurry and coats it on one side or both sides of the polyolefin diaphragm, and forms a stable coating structure after drying, and finally obtains a high-performance aramid microsphere and ceramic coated diaphragm. Compared with aramid oily coating, the cost of aramid nano-microspheres and ceramic particles mixed with water-based coating is lower, the coating method is simpler, and it is convenient for large-scale continuous production. In addition, compared with ceramic diaphragms, since aramid nano-microspheres have good affinity with electrolytes, the coated diaphragm has better wettability with electrolytes, thereby extending the cycle life of the battery, and the aramid nano-microspheres and ceramic mixed coated diaphragms optimize the transmission path of lithium ions, and the battery assembled by the diaphragm of the present invention has better ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the aramid nanospheres prepared in Example 1; Figure 2 This is a scanning electron microscope image of aramid nanospheres prepared in Example 2; Figure 3 This is a scanning electron microscope image of the cross-section of the aramid nano-microsphere and ceramic mixed coated diaphragm prepared in Example 4. DETAILED DESCRIPTION

[0018] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0020] A method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics, the preparation method comprising: S1. Preparation of modified meta-aramid stock solution: In an organic solvent, during the polymerization reaction of meta-aramid, a methylene group or an ether bond is introduced into the main chain of the meta-aramid to obtain a modified meta-aramid stock solution; S2. Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent are introduced into the precipitation device, subjected to high-speed shearing treatment by the precipitation device, cooled and then washed to obtain the modified aramid nano-microspheres; S3. Preparation of coating slurry: The coating slurry is obtained by uniformly dispersing aramid nano-microspheres, ceramic particles, a thickener, a binder and a wetting agent in water.

[0021] Specifically, in step S1, the preparation process of introducing methylene groups into the meta-aramid main chain to prepare the modified meta-aramid stock solution is as follows: Dissolving m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane in DMAC, and after being completely dissolved, performing a low-temperature polycondensation reaction, and after the reaction is completed, neutralizing and filtering the product to remove unreacted raw materials to obtain a methylene-substituted modified m-aramid stock solution; The preparation process of introducing ether bonds into the meta-aramid main chain to prepare modified meta-aramid stock solution is as follows: Dissolve meta-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether in DMAC, and after they are completely dissolved, perform a low-temperature polycondensation reaction. After the reaction is completed, neutralize and filter the product to remove unreacted reagents to obtain an ether-bonded modified meta-aramid stock solution.

[0022] Specifically, in the process of preparing the modified meta-aramid stock solution by introducing methylene into the meta-aramid main chain, the mass fraction of 4,4'-diaminodiphenylmethane in the modified meta-aramid polymer is 2%-30%; the molar ratio of the total molar number of meta-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:(0.95-1.05); In the process of preparing the modified meta-aramid stock solution by introducing ether bonds on the meta-aramid main chain, the mass fraction of 4,4'-diaminodiphenyl ether in the modified meta-aramid polymer is 2%-30%; the molar ratio of the total molar number of meta-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:(0.95-1.05).

[0023] Specifically, the low-temperature polymerization reaction temperature is 5-10° C., and the reaction time is 1-2 hours.

[0024] Specifically, the precipitation solvent includes water, DMAC and calcium chloride; the mass ratio of water, DMAC and calcium chloride is 100: (30-40): (2-4); the temperature of the precipitation solvent is 30-40°C.

[0025] Specifically, the solid content of the modified meta-aramid stock solution is 12-18%; the mass ratio of the modified meta-aramid stock solution to the precipitation solvent is 1:(5-20); In step S2, the stirring speed of the high-speed shear treatment is 1500-3000 r / min.

[0026] Specifically, in step S3, the mass ratio of water, aramid nanospheres, ceramic particles, thickener, binder and wetting agent is (22-25):1:(6-8):(0.05-0.07):(0.5-0.7):(0.05-0.07).

[0027] Specifically, the ceramic particles are at least one of aluminum oxide, silicon dioxide, magnesium hydroxide, zirconium dioxide, magnesium oxide, and boehmite.

[0028] Specifically, the thickener is at least one of a cellulose thickener, an inorganic salt thickener, and an amine oxide thickener; Specifically, the binder is a polyacrylate emulsion binder; more specifically, the binder is at least one of methyl acrylate, ethyl acrylate, butyl acrylate, and isooctyl acrylate; The wetting agent is at least one of siloxanes, fatty alcohol ethers and polyoxyethylene ethers.

[0029] More specifically, in step S3, pure water, aramid nanospheres, ceramic particles, thickener, binder and wetting agent are sequentially added into a planetary mixer for stirring and dispersion to obtain a coating slurry, wherein the stirring time is 30-40 min and the stirring speed is 30-40 r / min.

[0030] A method for preparing an aramid nano-microsphere and ceramic mixed coating diaphragm comprises the following steps: uniformly coating the coating slurry on a base film by micro-gravure coating, drying the base film, and rolling the base film to obtain the aramid nano-microsphere and ceramic mixed coating diaphragm.

[0031] Specifically, during the preparation of the diaphragm, the drying temperature is 145-155°C.

[0032] More specifically, the base film in the embodiment of the present invention is a 7 μm polyethylene diaphragm, but this is not a limitation to the present invention.

[0033] Example 1 (1) Preparation of methylene-substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenylmethane in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, the stirring speed is 800 r / min, and the reaction time is 1 hour. After the reaction is completed, the product is neutralized and filtered to remove the unreacted reagents, and a methylene-substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 15%.

[0034] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0035] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 1500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, methylated modified aramid nanospheres were obtained.

[0036] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 1 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 700-900 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (methyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred for 30 min. The stirring speed was controlled at 30 rpm to obtain a coating slurry.

[0037] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 2 μm on both sides was obtained.

[0038] Example 2 (1) Preparation of ether-substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenyl ether in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, with a stirring speed of 800 r / min and a reaction time of 1 hour. After the reaction is completed, the product is neutralized and filtered to remove unreacted reagents, and an ether-substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 18%.

[0039] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0040] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 1500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, ether-substituted aramid nanospheres were obtained.

[0041] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 1 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 700-900 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (ethyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred for 30 min. The stirring speed was controlled at 30 rpm to obtain a coating slurry.

[0042] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 1.7 μm on both sides was obtained.

[0043] Example 3 (1) Preparation of methylene-substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenylmethane in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, the stirring speed is 800 r / min, and the reaction time is 1 hour. After the reaction is completed, the product is neutralized and filtered to remove the unreacted reagents, and a methylene-substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 15%.

[0044] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0045] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 2500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, methylated modified aramid nanospheres were obtained.

[0046] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 1 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 700-900 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (butyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred for 30 min. The stirring speed was controlled at 30 rpm to obtain a coating slurry.

[0047] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 1.8 μm on both sides was obtained.

[0048] Example 4 (1) Preparation of ether bond substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenyl ether in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, with a stirring speed of 800 r / min and a reaction time of 1 hour. After the reaction is completed, the product is neutralized and filtered to remove unreacted reagents, and an ether bond substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 18%.

[0049] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0050] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 2500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, ether-substituted aramid nanospheres were obtained.

[0051] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 1 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 700-900 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (isooctyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred for 30 min at a stirring speed of 30 r / min to obtain a coating slurry.

[0052] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 1.5 μm on both sides was obtained.

[0053] Example 5 (1) Preparation of methylene-substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenylmethane in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, the stirring speed is 800 r / min, and the reaction time is 1 hour. After the reaction is completed, the product is neutralized and filtered to remove the unreacted reagents, and a methylene-substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 15%.

[0054] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0055] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 2500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, methylated modified aramid nanospheres were obtained.

[0056] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 1 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 300-500 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (methyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred for 30 min. The stirring speed was controlled at 30 rpm to obtain a coating slurry.

[0057] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 1.3 μm on both sides was obtained.

[0058] Example 6 (1) Preparation of ether bond substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenyl ether in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, with a stirring speed of 800 r / min and a reaction time of 1 hour. After the reaction is completed, the product is neutralized and filtered to remove unreacted reagents, and an ether bond substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 18%.

[0059] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0060] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 2500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, ether-substituted aramid nanospheres were obtained.

[0061] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 1 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 300-500 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (methyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred and dispersed for 30 min at a stirring speed of 30 rpm to obtain a coating slurry.

[0062] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 1 μm on both sides was obtained.

[0063] Example 7 (1) Preparation of methylene-substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane are dissolved in 82 kg of DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenylmethane in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, with a stirring speed of 800 r / min and a reaction time of 1 hour. After the reaction is completed, the product is neutralized and filtered to remove unreacted reagents to obtain a methylene-substituted modified meta-aramid stock solution, wherein the solid content of the modified meta-aramid stock solution is 15%.

[0064] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0065] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 3000 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, methylated modified aramid nanospheres were obtained.

[0066] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 1 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 300-500 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (methyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred for 30 min. The stirring speed was controlled at 30 rpm to obtain a coating slurry.

[0067] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 0.9 μm on both sides was obtained.

[0068] Example 8 (1) Preparation of ether bond substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenyl ether in the meta-aramid polymer is 2%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, with a stirring speed of 800 r / min and a reaction time of 1 hour. After the reaction is completed, the product is neutralized and filtered to remove unreacted reagents, and an ether bond substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 18%.

[0069] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:30:2, and the precipitation solvent temperature is 30°C.

[0070] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:5 and passed into the precipitation equipment. The stirring speed was 3000 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, ether-substituted aramid nanospheres were obtained.

[0071] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 22 kg of pure water, 6 kg of aramid nanosphere, 6 kg of aluminum oxide particles with a particle size of 300-500 nm, 0.07 kg of thickener sodium carboxymethyl cellulose, 0.5 kg of polyacrylate binder (methyl acrylate) and 0.05 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred for 30 min. The stirring speed was controlled at 30 rpm to obtain a coating slurry.

[0072] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 0.8 μm on both sides was obtained.

[0073] Example 9 (1) Preparation of modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether are dissolved in 82 kg of DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:1, and the mass fraction of 4,4'-diaminodiphenyl ether in the meta-aramid polymer is 30%. After complete dissolution, the temperature is maintained at 10°C, and a low-temperature polycondensation reaction is carried out, with a stirring speed of 800 r / min and a reaction time of 2 h. After the reaction is completed, the product is neutralized and filtered to remove unreacted reagents and catalysts, and an ether-substituted modified meta-aramid stock solution is obtained.

[0074] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The DMAC content is 40% by mass, the calcium chloride content is 4% by mass, and the precipitation solvent temperature is 40°C.

[0075] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:20 and introduced into the precipitation equipment at a stirring speed of 1500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, methylated modified aramid nanospheres were obtained.

[0076] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 25 kg of pure water, 1 kg of aramid nanosphere, 8 kg of aluminum oxide particles with a particle size of 700-900 nm, 0.05 kg of thickener sodium carboxymethyl cellulose, 0.7 kg of polyacrylate binder (methyl acrylate) and 0.07 kg of polyoxyethylene ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred and dispersed for 40 min at a stirring speed of 40 rpm to obtain a coating slurry.

[0077] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 155°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 2 μm on both sides was obtained.

[0078] Example 10 (1) Preparation of methylene-substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:0.95, and the mass fraction of 4,4'-diaminodiphenylmethane in the meta-aramid polymer is 30%. After complete dissolution, the temperature is maintained at 10°C, and a low-temperature polycondensation reaction is carried out, the stirring speed is 800 r / min, and the reaction time is 2 hours. After the reaction is completed, the product is neutralized and filtered to remove the unreacted reagents, and a methylene-substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 12%.

[0079] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:40:4, and the precipitation solvent temperature is 40°C.

[0080] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:20 and introduced into the precipitation equipment with a stirring speed of 2000 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, methylated modified aramid nanospheres were obtained.

[0081] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 25 kg of pure water, 1 kg of aramid nanosphere, 8 kg of silica with a particle size of 700-900 nm, 0.05 kg of amine oxide thickener (laurylamide propylamine oxide), 0.7 kg of polyacrylate binder (methyl acrylate) and 0.07 kg of silicone wetting agent (organic gemini polyether modified silicone) were added to a planetary mixer in sequence and stirred for 40 min. The stirring speed was controlled at 40 rpm to obtain a coating slurry.

[0082] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 145°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 2 μm on both sides was obtained.

[0083] Embodiment 11 (1) Preparation of ether bond substituted modified meta-aramid: m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether are dissolved in DMAC, wherein the molar ratio of the total molar number of m-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:1.05, and the mass fraction of 4,4'-diaminodiphenyl ether in the meta-aramid polymer is 15%. After complete dissolution, the temperature is maintained at 5°C, and a low-temperature polycondensation reaction is carried out, with a stirring speed of 800 r / min and a reaction time of 1 h. After the reaction is completed, the product is neutralized and filtered to remove unreacted reagents, and an ether bond substituted modified meta-aramid stock solution is obtained, wherein the solid content of the modified meta-aramid stock solution is 15%.

[0084] (2) Preparation of precipitation solvent: Mix water, DMAC and calcium chloride and stir them evenly. The mass ratio of water, DMAC and calcium chloride is 100:35:3, and the precipitation solvent temperature is 35°C.

[0085] (3) Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent were mixed in a mass ratio of 1:10 and introduced into the precipitation equipment. The stirring speed was 2500 r / min. The precipitation equipment was sheared at high speed to form precipitation fibers. Due to the increased flexibility of the molecular chain, the molecular chain curled into nanospheres. After cooling and washing, ether-substituted aramid nanospheres were obtained.

[0086] (4) Preparation of aramid nanosphere and ceramic mixed slurry: 23 kg of pure water, 1 kg of aramid nanosphere, 7 kg of zirconium dioxide particles with a particle size of 700-900 nm, 0.06 kg of inorganic salt thickener (pentasodium triphosphate), 0.6 kg of polyacrylate binder (methyl acrylate) and 0.06 kg of fatty alcohol ether wetting agent (fatty alcohol polyoxyethylene ether) were added to a planetary mixer in sequence and stirred and dispersed for 30 min at a stirring speed of 30 rpm to obtain a coating slurry.

[0087] (5) Preparation of diaphragm: The slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then the diaphragm was dried at a drying temperature of 150°C. After winding, a diaphragm coated with aramid nanospheres and ceramics with a coating thickness of 2 μm on both sides was obtained.

[0088] Comparative Example 1 The commercially available ceramic diaphragm has a total diaphragm thickness of 11 μm and a coating thickness of 4 μm.

[0089] Comparative Example 2 The coated diaphragm was prepared by the same method as in Example 1, except that the stirring speed in step (3) was reduced. The stirring speed in this comparative example 2 was 1000 r / min.

[0090] Comparative Example 3 The coated diaphragm was prepared by the same method as in Example 1, except that the stirring speed in step (3) was increased. The stirring speed in this comparative example 3 was 4000 r / min.

[0091] Comparative Example 4 The coated diaphragm was prepared by the same method as in Example 1, except that: in step (1) of this comparative example 4, 4'-diaminodiphenylmethane was not added, that is, the meta-aramid was not modified.

[0092] Comparative Example 5 The coated diaphragm was prepared by the same method as in Example 1, except that: in step (1) of this comparative example 5, the addition ratio of 4,4'-diaminodiphenylmethane was increased. In this comparative example 5, the mass fraction of 4,4'-diaminodiphenylmethane in the meta-aramid polymer was 40%.

[0093] Comparative Example 6 The coated diaphragm was prepared by the same method as in Example 1, except that the amount of aramid nanospheres added in step (4) of this comparative example 6 was increased, and 3 kg of aramid nanospheres were added in step (4) of this comparative example 6.

[0094] Comparative Example 7 The coated diaphragm was prepared by the same method as in Example 1, except that no aramid nano-microspheres were added to the coating slurry of Comparative Example 7.

[0095] Comparative Example 8 The coated diaphragm was prepared by the same method as in Example 1, except that the amount of wetting agent added in Comparative Example 8 was increased, and 0.15 kg of polyoxyethylene ether wetting agent was added in step (4) of Comparative Example 8.

[0096] Comparative Example 9 The coated diaphragm was prepared by the same method as in Example 1, except that the amount of wetting agent added in Comparative Example 9 was reduced, and 0.02 kg of polyoxyethylene ether wetting agent was added in step (4) of Comparative Example 9.

[0097] The performance of the diaphragms prepared in the above examples and comparative examples was tested, and the test results are shown in Tables 1 and 2. The test methods involved are: Thickness testing standard: GB / T 36363-2018; Tensile strength test standard: GB / T 36363-2018; Air permeability test standard: GB / T 36363-2018; Puncture strength test standard: GB / T 36363-2018; Thermal shrinkage test standard: GB / T 36363-2018; Liquid absorption test standard: GB / T 13542.2-2009; Film rupture temperature test standard: GB / T 36800.1-2018; Ionic conductivity test standard: GB / T 36363-2018.

[0098] The ion conductivity test requires the assembly of a soft-pack battery, in which the positive electrode is made of NCM811 material, the negative electrode is made of graphite material, and the electrolyte is lithium hexafluorophosphate, model: LBED8-240421. Specifically, it is assembled using a Kejing semi-automatic stacking machine through stacking, hot pressing, tab welding, top and side sealing, liquid injection, formation, and final sealing.

[0099] Table 1 Comparison of performance data of the diaphragm of the embodiment and the comparative example

[0100] Table 2 Ionic conductivity data of the diaphragms of the embodiments and comparative examples

[0101] From the data in Table 1 and Table 2 above, it can be seen that the diaphragms prepared by the preparation method of the present invention in Examples 1-11 have the characteristics of good wettability, high membrane rupture temperature, high puncture strength, excellent heat resistance, easy control of coating thickness, and high ionic conductivity. By introducing methylene or ether bonds on the main chain, the flexibility of the molecular chain is increased, and with different stirring speeds, aramid nano-microspheres with controllable particle size can be synthesized, which helps to control the coating thickness more accurately. Aramid microspheres of different particle sizes are matched with ceramic particles of different particle sizes to prepare slurry coated on the surface of polyethylene diaphragm, which can meet more coating requirements. The results of the embodiment show that the membrane rupture temperature of the diaphragm is significantly improved, and the wettability of the electrolyte is also significantly improved, which helps to improve the cycle life and safety of lithium batteries. Under 180°C, the aramid nano-microspheres and ceramic mixed coated diaphragms still maintain a good morphology, and the transverse and longitudinal thermal shrinkage can be controlled within 3%. In addition, compared with the ceramic diaphragm, the aramid nano-microspheres and ceramic mixed coated diaphragms have higher ionic conductivity. It is significantly better than the commercially available ceramic diaphragm in Comparative Example 1. Moreover, the aramid nano-microsphere and ceramic mixed coated diaphragm of the present invention has a simple production process and not only has excellent wettability and heat resistance, but also the coating thickness of the diaphragm can be precisely controlled, which is convenient for matching the actual working scene requirements of the battery diaphragm and industrial expansion of production, and can be widely used as a high-performance lithium-ion battery diaphragm.

[0102] Figure 1 This is a scanning electron microscope image of the aramid nanospheres prepared in Example 1; Figure 2 This is a scanning electron microscope image of the aramid nanospheres prepared in Example 2; Figure 1 and Figure 2 It can be seen that the diameter of the aramid nano-microspheres prepared in Example 1 is between 500 nm and 3.5 μm, and the diameter of the aramid nano-microspheres prepared in Example 2 is between 50 nm and 250 nm. Figure 3 This is a scanning electron microscope image of the cross section of the aramid nano-microsphere and ceramic mixed coated diaphragm prepared in Example 4. Figure 3 It can be seen that the coating thickness is about 1.5 μm.

[0103] From the comparison of the data of Comparative Example 2 and Example 1, it can be seen that if the stirring speed in step (3) is too low, the particle size of the aramid nano-microspheres will be too large, the coating thickness cannot be accurately controlled, and the coating thickness will be too large. Because the stirring speed is too low, the fibers cannot be fully stretched and refined in the coagulation bath, forming thicker fibers, which ultimately affects the air permeability of the membrane.

[0104] From the comparison of the data of Comparative Example 3 and Example 1, it can be seen that if the stirring speed of step (3) is too high, the structure of the aramid nano-microspheres will be destroyed and the performance of the coating film will be reduced, because the excessively high shear rate may cause the fibers to be subjected to excessive mechanical stress during the formation process, thereby destroying the structural integrity of the fibers, resulting in a decrease in the mechanical properties, air permeability and heat resistance of the diaphragm.

[0105] From the comparison of the data of Comparative Example 4 and Example 1, it can be seen that if the meta-aramid is not modified in step (1), it will lead to the failure to form aramid nano-microspheres, the coating thickness cannot be accurately controlled, and the coating thickness is too large. Because no methylene group is introduced for modification, the flexibility of the aramid molecular chain is not increased, and the molecular chain cannot be curled into low molecular weight nano-microspheres, resulting in a significant decrease in the air permeability of the diaphragm.

[0106] From the comparison of the data of Comparative Example 5 and Example 1, it can be seen that if the amount of the modified monomer 4,4'-diaminodiphenylmethane added in step (1) is too much, the particle size of the aramid nano-microspheres will be too small, and the coating thickness cannot be accurately controlled. If the coating thickness is too large, the aramid nano-microspheres are prone to agglomeration due to their small particle size, forming agglomerates of different sizes, resulting in a decrease in the air permeability of the diaphragm.

[0107] From the comparison of the data of Comparative Example 6 and Example 1, it can be seen that if the amount of aramid nanospheres added is increased, the thermal shrinkage performance of the diaphragm will deteriorate, affecting the safety performance of the battery, because the improvement of the thermal shrinkage performance of the diaphragm by ceramics is dominant.

[0108] From the comparison of the data of Comparative Example 7 and Example 1, it can be seen that if aramid nano-microspheres are not added to the coating slurry, the tensile strength, elongation at break, liquid absorption rate and membrane rupture temperature of the diaphragm will decrease, because aramid nano-microspheres can increase the mechanical properties and liquid absorption rate of the diaphragm and improve the membrane rupture temperature of the diaphragm.

[0109] From the data comparison between Comparative Example 8 and Example 1, it can be seen that if too much wetting agent is added to the coating slurry, the air permeability of the diaphragm will be too high. This is because when the wetting agent is used in excess, a denser film will be formed on the surface of the diaphragm, which will reduce the passage of gas through the diaphragm and cause a decrease in air permeability.

[0110] From the comparison of the data of Comparative Example 9 and Example 1, it can be seen that if the amount of wetting agent added to the coating slurry is too small, the membrane will be leaked, because if the amount of wetting agent added is insufficient, the surface tension may not be reduced to a sufficient degree, resulting in limited spreading ability of the liquid on the membrane surface. Therefore, the use of the wetting agent addition amount defined in the present invention is more conducive to obtaining a membrane with excellent performance.

[0111] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0112] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics, characterized in that: The preparation method is: S1. Preparation of modified meta-aramid stock solution: In an organic solvent, during the polymerization reaction of meta-aramid, a methylene bond or an ether bond is introduced into the main chain of the meta-aramid to obtain a modified meta-aramid stock solution; S2. Preparation of aramid nanospheres: The modified meta-aramid stock solution and the precipitation solvent are introduced into the precipitation device, subjected to high-speed shearing treatment by the precipitation device, cooled and then washed to obtain modified aramid nano-microspheres; S3. Preparation of coating slurry: The coating slurry is obtained by uniformly dispersing aramid nano-microspheres, ceramic particles, a thickener, a binder and a wetting agent in water.

2. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 1, characterized in that: In step S1, the preparation process of introducing methylene groups into the meta-aramid main chain to prepare a modified meta-aramid stock solution is as follows: Dissolving m-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenylmethane in DMAC, and after being completely dissolved, performing a low-temperature polycondensation reaction, and after the reaction is completed, neutralizing and filtering the product to remove unreacted raw materials to obtain a methylene-substituted modified m-aramid stock solution; The preparation process of introducing ether bonds into the meta-aramid main chain to prepare modified meta-aramid stock solution is as follows: Dissolve meta-phenylenediamine, isophthaloyl chloride and 4,4'-diaminodiphenyl ether in DMAC, and after they are completely dissolved, perform a low-temperature polycondensation reaction. After the reaction is completed, neutralize and filter the product to remove unreacted reagents to obtain an ether-bonded modified meta-aramid stock solution.

3. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 2, characterized in that: In the process of preparing a modified meta-aramid stock solution by introducing methylene groups into the meta-aramid main chain, the mass fraction of 4,4'-diaminodiphenylmethane in the modified meta-aramid polymer is 2%-30%; the molar ratio of the total molar number of meta-phenylenediamine and 4,4'-diaminodiphenylmethane to isophthaloyl chloride is 1:(0.95-1.05); In the process of preparing the modified meta-aramid stock solution by introducing ether bonds on the meta-aramid main chain, the mass fraction of 4,4'-diaminodiphenyl ether in the modified meta-aramid polymer is 2%-30%; the molar ratio of the total molar number of meta-phenylenediamine and 4,4'-diaminodiphenyl ether to isophthaloyl chloride is 1:(0.95-1.05).

4. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 2, characterized in that: The low-temperature polymerization reaction temperature is 5-10°C and the reaction time is 1-2h.

5. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 1, characterized in that: The precipitation solvent comprises water, DMAC and calcium chloride; the mass ratio of water, DMAC and calcium chloride is 100:(30-40):(2-4); the temperature of the precipitation solvent is 30-40°C.

6. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 1, characterized in that: The solid content of the modified meta-aramid stock solution is 12-18%; the mass ratio of the modified meta-aramid stock solution to the precipitation solvent is 1:(5-20); In step S2, the stirring speed of the high-speed shear treatment is 1500-3000 r / min.

7. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 1, characterized in that: In step S3, the mass ratio of water, aramid nanospheres, ceramic particles, thickener, binder and wetting agent is (22-25):1:(6-8):(0.05-0.07):(0.5-0.7):(0.05-0.07).

8. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 1, characterized in that: The ceramic particles are at least one of aluminum oxide, silicon dioxide, magnesium hydroxide, zirconium dioxide, magnesium oxide, and boehmite.

9. The method for preparing a mixed coating slurry of aramid nano-microspheres and ceramics according to claim 1, characterized in that: The thickener is at least one of a cellulose thickener, an inorganic salt thickener and an amine oxide thickener; The binder is at least one of methyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; The wetting agent is at least one of siloxanes, fatty alcohol ethers and polyoxyethylene ethers.

10. A method for preparing a diaphragm coated with a mixed aramid nano-microsphere and ceramic, characterized in that: The preparation method of the diaphragm is: coating the coating slurry evenly on the base film, and then drying to obtain the diaphragm; the coating slurry is prepared according to the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Ceramic aramid fiber coated diaphragm for lithium ion battery and preparation method of coated diaphragm

    CN110444714A

  • Reinforcing material for battery diaphragm

    CN104577011A

  • Preparation method of aramid 1314 copolymerized fibrid

    CN113105624A

  • Ceramic particle pore-forming aramid fiber coated lithium ion battery composite diaphragm and preparation method thereof

    CN114614196A

  • Composite diaphragm, preparation method thereof and lithium ion battery

    CN114865225A